Identification in Semitic languag:הדימוי בלשונות שמיות – מחקר השוואה (Journal of the College of Languages (JCL), 2014)
I studied in this research " simile tools " in Semitic Languages and the way to use it and what it′s common divisors .This research divided two chapters the first was a brief about simile in Semitic languages especially . Arabic , Hebrew and Syriac languages and the way of use it in each of this languages .At last we reach to conclusion in the end of this research About this common divisors and it has same origin but the environmental and social conditions changed part from this divisors .